2016
DOI: 10.1590/0104-9224/si2103.02
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Transfer Stability and Shielding Gas Composition on CO and CO2 Emissions during Short-circuiting MIG/MAG Welding

Abstract: Several studies have demonstrated the influence of parameters and shielding gas on metal transfer stability or on the generation of fumes in MIG/MAG welding, but little or nothing has been discussed regarding the emission of toxic and asphyxiating gases, particularly as it pertains to parameterization of the process. The purpose of this study was to analyze and evaluate the effect of manufacturing aspects of welding processes (short-circuit metal transfer stability and shielding gas composition) on the gas emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is the umbrella gas concentrator that is the physical model of such a process of accumulation of welding gas. Carbon monoxide would accumulate in the area located near the respiratory system of the worker, which is dangerous and can cause occupational diseases and contribute to the occurrence of other concomitant diseases, the study of which is highlighted in [14][15][16][17].…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the umbrella gas concentrator that is the physical model of such a process of accumulation of welding gas. Carbon monoxide would accumulate in the area located near the respiratory system of the worker, which is dangerous and can cause occupational diseases and contribute to the occurrence of other concomitant diseases, the study of which is highlighted in [14][15][16][17].…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…The paper does not specify the means of protection of employees. In article [14], the purpose of the study was to analyze and assess the impact of production aspects of welding processes (the stability of short-circuit metal transfer and protective gas composition) on the level of gas emissions during MIG/MAG welding (the aspects of labor and the environment protection). It was found that the richer the composition of protective gas in СО 2 , the more CO and СО 2 is formed by the arc.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Paper [10] provides an overview of welding fumes, their effect on health, and measures to protect welders against welding fumes. In the industrially developed countries, about 2 % of the workforce are employed in welding.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The use of mixtures with CO2 and pure CO2 as shielding gases emit significant amounts of CO2 and CO, capable of generating asphyxia and intoxication, respectively. The generation of these gases is not directly dependent on the arc stability and arc length, in the same proportion that the generation of fumes is sensitive to these factors, with the generation of CO2 and CO being greater according to the increase in the percentage of CO2 in the mixture used as shielding gas (MENESES; LEAL; SCOTTI, 2016).…”
Section: Introductionmentioning
confidence: 99%